The efficacy and safety of cabazitaxel in the treatment of metastatic castration-resistant prostate cancer: a systematic review and network meta-analysis based on randomized controlled trials - Cong Shao; Quan Wan; Jia Guo; Zhuo Chen (Frontiers in Pharmacology)
BackgroundCabazitaxel (CAB) has been approved for the treatment of patients with progressed metastatic castration-resistant prostate cancer (mCRPC) after receiving docetaxel. To assess the efficacy and safety of CAB in mCRPC patients through systematic review and network meta-analysis.MethodsRandomized controlled studies on the treatment of mCRPC with CAB in PUBMED, EMBASE, Cochrane, and Web of Science were searched. Relevant studies that met pre-set criteria were determined, and the quality of included studies was evaluated using the National Institutes of Health-Quality Assessment Tool. After the data was extracted, data analysis was conducted in R 4.3.2. Overall survival (OS), progression-free survival (PFS), and serious adverse events (SAEs) were used as the primary outcomes, and HR (hazard ratio) or RR (risk ratio) and their 95% confidence intervals (95% CrI) were calculated as effect sizes.ResultsA total of 13 studies were included, involving 5,814 patients. The overall risk of bias for 13 studies was low. The results showed that CAB 25 mg/m2 significantly improved OS compared to androgen receptor pathway inhibitor (ARPI) (1.50 [1.30, 1.70]) and MIT (1.40 [1.20, 1.70]), but its efficacy was inferior to Lu-PSMA (0.42 [0.27, 0.67]) and therapeutic drug monitoring (TDM)-CAB (0.51 [0.38, 0.70]). CAB 25 mg/m2 could significantly improve PFS compared to CAB + CP (1.40 [1.10, 2.00]), ARPI (1.80 [1.50, 2.30], MIT (1.40 [1.20, 1.60]), but its efficacy was not as good as CAB 20 mg/m2 (0.92 [0.82, 1.00]), Lu-PSMA (0.58 [0.41, 0.80]), TDM-CAB (0.67 [0.51, 0.86]). In addition, compared to CAB 25 mg/m2, CAB + CP may significantly increase the risk of SAEs (3.10 [1.70, 5.90]).ConclusionCAB is an effective treatment in mCRPC, and combining it with other treatment methods may enhance efficacy, but attention should be paid to the occurrence of adverse events.